Pemutusan Hubungan Kerja bagi Pekerja - Nabila, Jihan Sulistia; Santoso, Imam Budi; Mubina, Rohendra Fatham (Legal Spirit, 2024)
Workers or laborers have the right to obtain protection for safety and health, morals and decency, as well as treatment in accordance with human dignity and religious values. Termination of Employment is one of the problems in employment that often occurs. Termination of employment causes anxiety because it has a negative impact on the survival and future of workers and their families. As an effort to protect workers or laborers affected by Termination of Employment, in 2021 the Government issued a new policy, namely Government Regulation Number 37 of 2021 concerning the Implementation of the Job Loss Guarantee Program. This research aims to find out and analyze the Job Loss Guarantee program and its implementation in Karawang Regency. This research uses a normative legal research method by examining theories, concepts, legal principles and statutory regulations related to this research. The Job Loss Guarantee Program is provided to workers or laborers affected by Termination of Employment in the form of cash benefits, career counseling benefits, job training benefits, and job market information benefits. This guarantee program came into effect in Karawang Regency on February 11 2022 a year after the regulations were issued with the number of participants who have claimed benefits during 2022 amounting to 683 participants and the total funds disbursed amounting to IDR. 1,385,714,400.00. However, the implementation of this guarantee program in Karawang Regency is still not optimal because there are several technical problems in the benefit claim process